First report of Cryptosporidium spp. oocysts in stool of Adelie penguin from the Antarctic using acid-fast stain - Fredes, Fernando; Raffo, Eduardo; Muñoz, Pamela (Antarctic Science, 2007)
Artículo de Publicación ISI